Enzymatic synthesis of novel corylifol A glucosides via a UDP-glycosyltransferase. (29th June 2017) - Li, Nan; Miao, Jian; Li, Jing; Zhao, Yu-Ru; Li, Hong-Mei; Dai, Yi-Qun; Huo, Qiang; Wu, Cheng-Zhu; Ma, Tao
Abstract: Corylifol A, a member of the isoflavone subclass of isoflavonoids, has long been considered to have various biological activities. Here, we sought to synthesize corylifol A glucosides by the in vitro glucosylation reaction using the UDP-glycosyltransferase YjiC from Bacillus licheniformis DSM 13, and obtained two novel glucosides: corylifol A-4′, 7-di- O -beta-d -glucopyranoside (1 ) and corylifol A-4′- O -beta-d -glucopyranoside (2 ). To improve the yield of the products, the reaction time, concentration of UDP-glucose, and pH of the buffer were optimized. The Michaelis constant (Km ) was calculated to be 2.88 mM, and the maximal velocity (Vmax ) was calculated to be 77.32 nmol/min/mg for UDP-glycosyltransferase. Meanwhile, the water-solubility of compounds1 and2 was approximately 27.03 and 15.13 times higher, respectively, than that of their parent compound corylifol A. Additionally, the corylifol A glycosylated products exhibited the highest stability at pH 9.6 and better temperature stability than corylifol A at 40, 60, 80 and 100 °C. In addition, cytotoxicity activity assays against three human tumor cell lines, only corylifol A showed moderate anti-proliferative activity. Overall, this work demonstrates that glycosylation can enhance the water solubility and stability of promising compounds, with potential for further development and application. Graphical abstract: Highlights: Yjic is a glycosyltransferase that can confer modifications to corylifol A. Glucosylation with Yjic was optimized to obtain two novel corylifol A glucosides. Glycosylation of compounds can improve water solubility and stability.